Public Health Response to Aedes aegypti and Ae. albopictus Mosquitoes Invading California, USA - Porse, Charsey Cole (Emerg Infect Dis, 2015)
Aedes aegypti and Ae. albopictus mosquitoes, primary vectors of dengue and chikungunya viruses, were recently detected in California, USA. The threat of potential local transmission of these viruses increases as more infected travelers arrive from affected areas. Public health response has included enhanced human and mosquito surveillance, education, and intensive mosquito control.